THE RELATIONSHIP OF FAMILY SUPPORT WITH THE LEVEL OF PRE-ANESTHESIAN SECTIO PATIENTS IN THE HOSPITAL PEKALONGAN REGIONAL GENERAL - Vika Andriyani; Roro Lintang Suryani; Asmat Burhan (Global Indonesia Health Care (GOICARE), 2024)
Background: Sectio Caesarea (SC) is a surgical procedure to save a mother and baby. Most SC preoperative patients experience mild and severe anxiety; this anxiety will affect the patient's recovery process. Anxious conditions cause vasoconstriction of blood vessels, so that blood supply to the heart decreases. One of the other factors causing anxiety in preoperative patients is family support. Families who always support the patient's recovery will be able to reduce patient anxiety. Objective: The purpose of this study was to determine the relationship between family support and the pre-anesthesia anxiety level of sectio-caesarea patients at Bendan Pekalongan Hospital. Methods: Using quantitative observational and analytic research methods with a cross-sectional approach. The place of research was in the reception room of IBS Bendan Pekalongan Hospital. sample 36 patients with consecutive sampling techniques. Data analysis in the form of bivariate data produces the frequency distribution and percentage of each variable. Results: The results of the correlation coefficient of -493** indicate that there is a fairly strong and significant correlation with a negative or unidirectional direction, meaning that the greater the level of family support, the lower the patient's anxiety level. Conclusion: The results of the spearman rank test analysis of 36 respondents showed a p value of 0.001, <0.05, which means that there is a relationship between family support and the level of pre-anesthesia anxiety of Sectio Caesarea patients at Bendan Pekalongan Regional General Hospital. Keywords: Family support, anxiety level, and pre-anesthesia of Sectio Caesarea patient